Clade Ib: a new emerging threat in the Mpox outbreak - Srivastava, Shriyansh; Laxmi,; Sharma, Khyati; Sridhar, Sathvik Belagodu; Talath, Sirajunisa; Shareef, Javedh; Mehta, Rachana; Satapathy, Prakisini; Sah, Ranjit (Frontiers in Pharmacology, 2024)
Monkeypox, a zoonotic virus in the Orthopoxvirus genus, has drawn global attention for its impact on public health. In the current Mpox outbreak, a novel clade, Ib, has emerged as a significant and potentially fatal threat. This review examines the dynamics of MPXV transmission, person-to-person spread, and infection mechanisms, highlighting key risk factors. We explore the clinical features of Mpox, focusing on symptomology, illness duration, and the distinguishing characteristics of clade Ib compared to other clades. A critical analysis addresses diagnostic techniques and emphasizes the need for robust surveillance, particularly for clade Ib detection. We review recent prevention and treatment strategies, including antiviral drugs and vaccines, with a focus on clade Ib containment. The conclusion underscores the urgency of global collaboration to prevent and prepare for emerging threats like clade Ib and identifies crucial research paths and knowledge gaps. This review offers a comprehensive overview of clade Ib, covering its emergence, genetic traits, epidemiological impact, transmission patterns, clinical features, the role of Artificial Intelligence (AI) in outbreak management, detection challenges, and implications for public health response.